2015
DOI: 10.1007/s11244-015-0392-y
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite UZM-8: Synthesis, Characterization, and Catalytic Properties in Isopropylation of Benzene with 2-Propanol

Abstract: The synthesis of zeolite UZM-8 with disordered MWW monolayers in the presence of diethyldimethylammonium hydroxide as the sole structuredirecting agent is described. Under the synthesis conditions studied here, crystallization of pure UZM-8 was possible only from synthesis mixtures with a narrow range (15-25) of Si/Al ratios. The physicochemical properties of H-UZM-8 and its catalytic properties for the isopropylation of benzene to form cumene are compared with those obtained from the other members of MWW fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The 2D zeolites are usually made from exfoliation [18][19][20][21][22][23][24] and pillaring [6,15,[25][26][27][28][29][30] of the 2D zeolite precursors that contain stacked zeolite nanosheets of one-to-two unit cell or smaller thickness. The catalytic tests have shown that the delaminated and pillared 2D zeolites have improved activity and lifetime with respect to their 3D microporous counterparts in processing bulky molecules [18,[31][32][33][34][35]. 4 Despite these practices in synthesis and catalytic tests of the unit-cell thick 2D zeolite catalysts, evaluation of acid site locations and the catalytic behaviors of acid sites at each location has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D zeolites are usually made from exfoliation [18][19][20][21][22][23][24] and pillaring [6,15,[25][26][27][28][29][30] of the 2D zeolite precursors that contain stacked zeolite nanosheets of one-to-two unit cell or smaller thickness. The catalytic tests have shown that the delaminated and pillared 2D zeolites have improved activity and lifetime with respect to their 3D microporous counterparts in processing bulky molecules [18,[31][32][33][34][35]. 4 Despite these practices in synthesis and catalytic tests of the unit-cell thick 2D zeolite catalysts, evaluation of acid site locations and the catalytic behaviors of acid sites at each location has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, synthesis protocols offer a large space for further improvements in terms of external surface areas and accessible acid site concentrations. At the same time, all layered MWW zeolites outperformed their 3D counterpart (MCM‐22) with respect to both conversion and selectivity . The presence of mesoporosity between the lamellar MFI nanosheets is behind the observed increase of indole conversion compared to 3D MFI zeolite (from 4 to 97%) and selectivity to 3‐acetylindole (from 30 to 75%) in the indole acylation reaction …”
Section: D Zeolitesmentioning
confidence: 90%
“…[ 127 ] Similarly, the alkylation of benzene to ethylbenzene and cumene took place more effi cient over the directly-synthesized MCM-56 [ 128,129 ] or the post-modifi ed MCM-56 analogue [ 130 ] than conventional MCM-22 catalyst, and the deactivation rate was quite slow, probably because the active sites on external surface were more open to outside and did not get infl uenced by the micropore blockage. In comparison to the common view that the catalytic reactions mainly occurred inside zeolite channels, the external surfaces of MWW zeolite were highly active for the synthesis of ethylbenzene and cumene.…”
Section: Acid-catalyzed Reactionsmentioning
confidence: 99%
“…Taking advantages of large external surface, the delaminated ITQ‐2 exhibited superior catalytic activity in the alkylation of biphenyl and benzene with propylene . Similarly, the alkylation of benzene to ethylbenzene and cumene took place more efficient over the directly‐synthesized MCM‐56 or the post‐modified MCM‐56 analogue than conventional MCM‐22 catalyst, and the deactivation rate was quite slow, probably because the active sites on external surface were more open to outside and did not get influenced by the micropore blockage. Expected for Friedel‐Crafts alkylation, the delaminated Al‐MWW, prepared by the exfoliation of ERB‐1P and Al substitution, was reported to facilitate the formation of 1‐acetyl‐2‐methoxynaphthalene in the Friedel‐Crafts acylation of 2‐methoxynaphthalene with acetic anhydride .…”
Section: Catalytic Applications Of Layered Zeolite Materialsmentioning
confidence: 99%